Fabricated energy-saving thermal-insulation board based on variable-temperature foaming and preparation method of fabricated energy-saving thermal-insulation board

Through the prefabricated energy-saving and insulated plate preparation method based on variable temperature foaming, combined with blast furnace slag powder and solid waste-based sulfur aluminum-ferrous aluminum-type gelled clinker, and using medium-temperature heat sources to catalyze the foaming and curing process, the problems of high energy consumption and carbon emissions of the existing plate preparation process are solved, and the improvement of strength and pore structure and low-carbon sustainable development are achieved.

CN119528533AActive Publication Date: 2025-02-28国舜绿建科技有限公司 +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411271852.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-02-28
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

The preparation process of existing prefabricated energy-saving and thermal insulation boards requires high-temperature and high-pressure autoclave maintenance, resulting in high energy consumption and carbon emissions. The strength and pore structure of the autoclaved sheet are insufficient, and the foaming process is uneven.

Method used

The prefabricated energy-saving and insulated plate preparation method based on variable temperature foaming is adopted, and the blast furnace slag powder, solid waste-based sulfur aluminum-ferrous aluminum-type gelled clinker, by-product gypsum and other raw materials are used to combine a low-alkaline gelling system and a hydrogen peroxide foaming agent, and the foaming and curing process is achieved by using a medium-temperature heat source to achieve controllable foam expansion and hardening.

Benefits of technology

It reduces the energy consumption and carbon emissions of the preparation process, improves the strength of the plate and the uniformity of the pore structure, and realizes the low-carbon and sustainable development of energy-saving insulation materials, and the overall carbon footprint can be reduced by more than 70%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528533A_ABST
    Figure CN119528533A_ABST
Patent Text Reader

Abstract

The invention provides a variable temperature foaming-based assembled energy-saving thermal insulation board, which is prepared from the following raw materials in parts by mass: 60 to 80 parts of blast furnace slag powder, 10 to 20 parts of solid waste-based sulfur aluminum iron series gelling clinker, 10 to 25 parts of original byproduct gypsum, 2 to 6 parts of silica fume, 0.5 to 2 parts of carbide slag, 0.5 to 1.2 parts of calcium stearate, 0.2 to 0.6 part of polycarboxylate superplasticizer and 0.02 to 0.1 part of xanthan gum. 0.2 to 1 part of dispersible latex powder, 0.1 to 0.5 part of chopped fiber, 0.02 to 0.06 part of composite retarder, and a foaming agent; according to the method, hydrogen peroxide is selected as a foaming agent, and due to the low alkalinity characteristic of a gelling system, the hydrogen peroxide cannot be quickly decomposed after being added, so that the stirring time after the hydrogen peroxide is added can be prolonged, and meanwhile, it is guaranteed that fresh slurry has the high flow state characteristic. After the mixed slurry is poured into a mold, decomposition of hydrogen peroxide is catalyzed by applying a medium-temperature heat source, and at the moment, the foaming expansion process of the fresh slurry is parallel to the curing and hardening process, so that controllable regulation and control of the foaming process are realized, and the hardening speed of the slurry is increased. Finally, the solid waste-based energy-saving thermal insulation board for the fabricated building is prepared on the basis of variable-temperature foaming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solid waste-based energy-saving thermal insulation materials, and in particular relates to an assembled energy-saving thermal insulation board based on variable temperature foaming and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Carbon emissions from buildings are one of the sources of greenhouse gases. The development of high-performance, low-energy energy-saving insulation panels for prefabricated buildings is of great significance for improving the energy efficiency of buildings, reducing the carbon footprint of the entire life cycle of buildings, and promoting the green transformation and sustainable development of prefabricated buildings. At present, prefabricated energy-saving insulation panels are generally based on autoclaved aerated concrete panels, but their preparation process must be cured in an autoclave at 180-200℃ and 1.1-2MPa saturated steam pressure for 8-24 hours. This curing process is accompanied by high energy consumption and CO2 emissions, and the environmental impact it brings accounts for about 20% of the overall environmental impact of autoclaved aerated concrete panels. In addition, its raw materials usually require cement, lime and quartz sand. The cement and lime industries account for about 8% and 1% of global anthropogenic CO2 emissions, respectively. Excessive exploitation of sand and gravel seriously threatens the stability of river channels and river ecosystems. These not only limit the low-carbon sustainable development of energy-saving insulation materials for prefabricated buildings, but also lead to environmental degradation. As for autoclaved aerated concrete, on the one hand, the early performance of the product is insufficient, which is easy to cause problems such as the collapse of the energy-saving insulation panel structure. On the other hand, the chemical foaming process is often very intense, and a too fast foaming process is not conducive to the formation of a uniform pore structure. At the same time, too fast foaming causes the slurry to thicken greatly, which places high demands on the mixing and pouring equipment. Therefore, the strength development of the autoclave-free energy-saving insulation board is difficult to match with the foaming expansion process. Summary of the invention

[0004] In order to solve the above problems, the present invention provides an assembled energy-saving insulation board based on variable temperature foaming and a preparation method thereof, aiming to achieve performance improvement and overall energy consumption reduction of solid waste-based assembled energy-saving insulation board through mild curing means.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] In view of the high carbon emissions and energy consumption of existing autoclaved aerated concrete board raw materials and maintenance processes; the dual disadvantages of strength and pore structure of autoclaved-free energy-saving insulation boards; and the mismatch between substrate strength development and rapid foaming and expansion process in the chemical foaming process, the present invention provides an assembled energy-saving insulation board based on variable temperature foaming and a preparation method thereof.

[0007] The first aspect of the present invention provides an assembled energy-saving thermal insulation board based on variable temperature foaming, which is composed of the following raw materials in parts by mass: 60-80 parts of blast furnace slag powder, 10-20 parts of solid waste-based sulfur-aluminum-iron cementitious clinker, 10-25 parts of original by-product gypsum, 2-6 parts of silica fume, 0.5-2 parts of carbide slag, 0.5-1.2 parts of calcium stearate, 0.2-0.6 parts of polycarboxylate water reducer, 0.02-0.1 parts of xanthan gum, 0.2-1 parts of dispersible latex powder, 0.1-0.5 parts of chopped fibers, 0.2-0.6 parts of composite retarder, and a foaming agent;

[0008] The foaming agent is a hydrogen peroxide solution with a mass concentration of 30%, and the amount used is 2-5% of the total mass of the gelling material. In addition, industrial-grade hydrogen peroxide solutions with concentrations of 27.5% and 35% are also suitable.

[0009] In some embodiments, the water-to-cement ratio is 0.3-0.4.

[0010] In some embodiments, the solid waste-based sulfur-aluminum-iron cementitious clinker is made from coal gangue, red mud, aluminum ash, carbide slag, and by-product gypsum through low-temperature calcination at 1200-1250°C.

[0011] The slag continuously dissolves silicon-aluminum ions in the vitreous body under the supersulfate and sulphoaluminate system, which can participate in the synthesis of AFt and CSH gel, compact the structure and improve the later performance. At the same time, as a solid waste, its source is more low-carbon and sustainable.

[0012] In some embodiments, the composite retarder consists of boric acid, citric acid and tartaric acid in a composition ratio of 1:1:2.

[0013] In some embodiments, the chopped fibers are made of polypropylene fibers, glass fibers, etc., and have a length of 6-12 mm.

[0014] The second aspect of the present invention provides a method for preparing an assembled energy-saving thermal insulation board based on variable temperature foaming, comprising:

[0015] Solid waste-based sulfur-aluminum-iron cementitious clinker, blast furnace slag powder, silica fume, and carbide slag are ground separately and premixed to obtain a first mixed material;

[0016] Adding calcium stearate, xanthan gum, and dispersible latex powder to the first mixed material, and mixing them evenly to obtain a second mixed material;

[0017] The original by-product gypsum, polycarboxylate water reducer, chopped fibers, composite retarder and water are wet-mixed uniformly at a water-cement ratio of 0.3-0.4 to obtain a water-containing mixture;

[0018] The second mixed material is mixed with the water-containing mixed material, firstly stirred at a slow speed for 30-40 seconds, and then stirred at a high speed for 3-4 minutes to obtain a mixed slurry; wherein, during the slow stirring process, hydrogen peroxide is added, and then stirred at a high speed for 1 minute;

[0019] The mixed slurry is poured into a board mold box, and after the mold box is covered with a film, the board temperature is maintained at 40-60° C. for 12-24 hours by external heating, demolded, and cured.

[0020] The present invention utilizes the low alkalinity characteristics of the gelling system and the medium-temperature decomposition and gas production characteristics of hydrogen peroxide. After the initial addition of hydrogen peroxide, it will not actively decompose, which can improve the uniformity of hydrogen peroxide and ensure that the fresh slurry has high fluidity characteristics. After the mixed slurry is poured into the mold, the decomposition of hydrogen peroxide is catalyzed by applying a medium-temperature heat source. At this time, the foaming and expansion process of the fresh slurry is parallel to the curing and hardening process, thereby achieving controllable regulation of the foaming process and improving the slurry hardening speed.

[0021] In some embodiments, the first mixed material has a fineness of less than 10% on a 200-mesh square-hole sieve.

[0022] In some embodiments, the rotation speed of the slow stirring is 140±5 r / min, which depends on the disturbance state of the stirring teeth in the stirring tank. If the disturbance is small, it is recommended to increase the rotation speed appropriately.

[0023] In some embodiments, the rotation speed of the high-speed stirring is 280±10 r / min, which depends on the disturbance state of the stirring teeth in the stirring tank. If the disturbance is small, it is recommended to increase the rotation speed appropriately.

[0024] More specifically, they include:

[0025] (1) Solid waste-based sulfur-aluminum-iron cementitious clinker is made from coal gangue, red mud, aluminum ash, carbide slag, and by-product gypsum through low-temperature calcination at 1200-1250℃.

[0026] (2) taking 10-20 parts of the solid waste-based sulfur-aluminum-iron cemented clinker in (1), 60-80 parts of blast furnace slag powder, 2-6 parts of silica fume, and 0.5-2 parts of calcium carbide slag, grinding and premixing the mixture, and the fineness requirement is that the residue on a 200-mesh square hole sieve is less than 10%;

[0027] (3) adding 0.5-1.2 parts of calcium stearate, 0.02-0.1 parts of xanthan gum, and 0.2-1 parts of dispersible latex powder to the mixture in (2), mixing well and setting aside;

[0028] (4) 10-25 parts of original by-product gypsum, 0.2-0.6 parts of polycarboxylate water reducer, 0.1-0.5 parts of chopped fibers, 0.02-0.06 parts of composite retarder, 0.3-0.4 parts of water-cement ratio, 30-40 parts of water, wet-mix and stir, and set aside;

[0029] (5) taking the mixture in (3) and mixing it into the aqueous mixture in (4), first stirring at a slow speed for 30 seconds and then stirring at a high speed for 3 minutes to prepare a mixed slurry;

[0030] (6) While the mixed slurry in (5) is being slowly stirred, 2-5 parts of hydrogen peroxide is added, followed by high-speed stirring for 1 minute;

[0031] (7) The fresh slurry mixed in (6) is poured into a board mold box, and the mold box is covered with plastic wrap. The board temperature is maintained at 40-60°C for 12-24 hours by external heating. The assembled energy-saving insulation material is finally demolded after expansion and hardening. After that, the assembled energy-saving insulation board is obtained by proper curing in a standard curing room.

[0032] The third aspect of the present invention provides the application of the above-mentioned assembled energy-saving thermal insulation board based on variable temperature foaming in the field of construction.

[0033] Beneficial effects of the present invention

[0034] (1) Compared with the existing technology, the assembled energy-saving and thermal insulation board prepared by the present invention eliminates the high temperature and high pressure and steam curing steps in the autoclave in the production process, making the preparation process simpler and safer, and greatly reducing the equipment investment. In terms of the selection of raw materials, almost all of them come from bulk industrial solid waste. The source of the strength of the material: give full play to the potential hydration activity of blast furnace slag powder in the persulfate system, make use of the early strength, fast hardening and high strength characteristics of solid waste-based sulfur-aluminum-iron cementitious materials, compound silica fume and calcium carbide slag as slurry function regulators, and finally realize a hardening system with C(A)-SH and AFt as the main hydration products. In the foaming process of the material, most of the existing technologies use aluminum powder or hydrogen peroxide as the foaming agent. And all technologies are rapid and violent gas expansion after the foaming agent is added to the fresh slurry, which leads to a rapid decrease in the flow state of the fresh slurry and an increase in consistency. This is not conducive to the high-precision molding of the slurry during the casting process. The present invention chooses hydrogen peroxide as a foaming agent. Due to the low alkalinity of this gelling system, hydrogen peroxide does not decompose quickly after being added, which can extend the stirring time after the addition of hydrogen peroxide, while ensuring that the fresh slurry has high fluidity. After the mixed slurry is poured into the mold, the decomposition of hydrogen peroxide is catalyzed by applying a medium-temperature heat source. At this time, the foaming and expansion process of the fresh slurry is parallel to the curing and hardening process, thereby achieving controllable regulation of the foaming process and improving the slurry hardening speed. Finally, the present invention prepares a solid waste-based energy-saving insulation board for prefabricated buildings based on variable temperature foaming.

[0035] (2) The raw materials of the present invention are almost all taken from industrial solid waste. The slurry expansion and matrix hardening are achieved through variable temperature curing under mild conditions, and the product has excellent comprehensive performance.

[0036] (3) The cementitious system of the present invention belongs to a persulfate slag system, which fully exploits the hydration activity of blast furnace slag in the persulfate system, takes advantage of the early strength, fast hardening and high strength characteristics of solid waste-based sulfur-aluminum-iron cementitious materials, and compounded silica fume and carbide slag as slurry function regulators, ultimately achieving a hardening system with C(A)-SH and AFt as the main hydration products. The product raw material end and the process end are more energy-efficient, and the overall carbon footprint can be reduced by more than 70%.

[0037] (4) The present invention catalyzes the decomposition of hydrogen peroxide by applying a medium-temperature heat source. At this time, the foaming and expansion process of the fresh slurry is carried out in parallel with the curing and hardening process, thereby achieving controllable regulation of the foaming process and improving the slurry hardening speed.

[0038] (5) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0040] Figure 1 Process flow chart of the present invention;

[0041] Figure 2 A diagram of the pore structure of the energy-saving and heat-insulating material of the present invention. DETAILED DESCRIPTION

[0042] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0043] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0044] In the following embodiments, solid waste-based sulfur-aluminum-iron cementitious clinker is prepared by low-temperature calcination at 1220° C. using 16 parts of coal gangue, 10 parts of red mud, 30 parts of aluminum ash, 23 parts of carbide slag, and 25 parts of by-product gypsum as raw materials, and is set aside.

[0045] Polycarboxylate water reducer, brand name Sika, commercially available product.

[0046] Example 1

[0047] The invention discloses an assembled energy-saving thermal insulation board based on variable temperature foaming. The energy-saving thermal insulation board uses blast furnace slag powder, solid waste-based sulfur-aluminum-iron cementitious clinker, and original desulfurized gypsum as main cementitious materials, uses carbide slag, silica fume, etc. as solid waste-based functional regulators, uses calcium stearate and xanthan gum as foam stabilizers, uses dispersible latex powder as pore enhancer, uses short-cut fibers as toughening materials, uses polycarboxylic acid water reducer and composite retarder as rheology regulators, and uses 30% hydrogen peroxide as a foaming agent. The water meets the requirements for concrete mixing water. The foaming process adopts unique variable temperature foaming to achieve balanced stability of slurry expansion and hardening under mild conditions.

[0048] An assembled energy-saving thermal insulation board based on variable temperature foaming and a preparation method thereof, comprising the following steps:

[0049] (1) The solid waste-based sulphur-aluminum-iron cemented clinker is prepared by calcining at 1220°C with 16% coal gangue, 10% red mud, 30% aluminum ash, 23% carbide slag and 25% by-product gypsum as raw materials, and is prepared for use. The main mineral phases are Fe-Al soluble calcium sulphoaluminate, anhydrous calcium sulphoaluminate, dicalcium silicate and iron phases;

[0050] (2) taking 20 parts of the solid waste-based sulfur-aluminum-iron cemented clinker in (1), 60 parts of blast furnace slag powder, 2 parts of silica fume, and 1 part of calcium carbide slag, grinding and premixing them, and the fineness requirement is to meet the sieve residue of 200 mesh square hole sieve less than 10%;

[0051] (3) Add 0.8 parts of calcium stearate, 0.04 parts of xanthan gum, and 0.5 parts of dispersible latex powder to the mixture in (2), mix well and set aside;

[0052] (4) 20 parts of original by-product gypsum, 0.4 parts of polycarboxylate water-reducing agent, 0.2 parts of chopped fibers, 0.06 parts of composite retarder, and 30 parts of water were mixed and stirred by a wet method for later use;

[0053] (5) The mixture in (3) is mixed into the water-containing mixture in (4), first stirred at a slow speed (145 r / min) for 30 seconds, and then stirred at a high speed (285 r / min) for 3 minutes to prepare a mixed slurry;

[0054] (6) The mixed slurry in (5) was slowly stirred (145 r / min), and 3 parts of hydrogen peroxide was added during the slow stirring process, and then stirred at a high speed (285 r / min) for 1 min;

[0055] (7) The fresh slurry mixed in (6) is poured into a board mold box, and the mold box is covered with plastic wrap. The board temperature is maintained at 40°C for 24 hours by external heating. The assembled energy-saving insulation material is finally demolded after expansion and hardening. After that, the assembled energy-saving insulation board is obtained by proper curing in a standard curing room.

[0056] Example 2

[0057] The invention discloses an assembled energy-saving thermal insulation board based on variable temperature foaming. The energy-saving thermal insulation board uses blast furnace slag powder, solid waste-based sulfur-aluminum-iron cementitious clinker, and original desulfurized gypsum as main cementitious materials, uses carbide slag, silica fume, etc. as solid waste-based functional regulators, uses calcium stearate and xanthan gum as foam stabilizers, uses dispersible latex powder as pore enhancer, uses short-cut fibers as toughening materials, uses polycarboxylic acid water reducer and composite retarder as rheology regulators, and uses 30% hydrogen peroxide as a foaming agent. The water meets the requirements for concrete mixing water. The foaming process adopts unique variable temperature foaming to achieve balanced stability of slurry expansion and hardening under mild conditions.

[0058] An assembled energy-saving thermal insulation board based on variable temperature foaming and a preparation method thereof, comprising the following steps:

[0059] (1) Solid waste-based sulphur-aluminum-iron cementitious clinker is made from coal gangue, red mud, aluminum ash, carbide slag, and by-product gypsum by calcining at 1200°C for use. Its main mineral phases are composed of Fe-Al soluble calcium sulphoaluminate, anhydrous calcium sulphoaluminate, dicalcium silicate, and iron phases;

[0060] (2) taking 15 parts of the solid waste-based sulfur-aluminum-iron cemented clinker in (1), 70 parts of blast furnace slag powder, 4 parts of silica fume, and 1.5 parts of calcium carbide slag, grinding and premixing the mixture, and the fineness requirement is that the residue on a 200-mesh square sieve is less than 10%;

[0061] (3) Add 1 part of calcium stearate, 0.06 part of xanthan gum, and 0.8 part of dispersible latex powder to the mixture in (2), mix well and set aside;

[0062] (4) 15 parts of original by-product gypsum, 0.5 parts of polycarboxylate water-reducing agent, 0.3 parts of chopped fibers, 0.04 parts of composite retarder, and 35 parts of water were mixed and stirred by a wet method for later use;

[0063] (5) The mixture in (3) is mixed into the water-containing mixture in (4), first stirred at a slow speed (145 r / min) for 30 seconds, and then stirred at a high speed (285 r / min) for 3 minutes to prepare a mixed slurry;

[0064] (6) The mixed slurry in (5) was slowly stirred (145 r / min), and 4 parts of hydrogen peroxide were added during the slow stirring process, and then stirred at a high speed (285 r / min) for 1 min;

[0065] (7) The fresh slurry mixed in (6) is poured into a board mold box, and the mold box is covered with plastic wrap. The board temperature is maintained at 50°C for 16 hours by external heating. The assembled energy-saving insulation material is finally demolded after expansion and hardening. After that, the assembled energy-saving insulation board is obtained by proper curing in a standard curing room.

[0066] Example 3

[0067] The invention discloses an assembled energy-saving thermal insulation board based on variable temperature foaming. The energy-saving thermal insulation board uses blast furnace slag powder, solid waste-based sulfur-aluminum-iron cementitious clinker, and original desulfurized gypsum as main cementitious materials, uses carbide slag, silica fume, etc. as solid waste-based functional regulators, uses calcium stearate and xanthan gum as foam stabilizers, uses dispersible latex powder as pore enhancer, uses short-cut fibers as toughening materials, uses polycarboxylic acid water reducer and composite retarder as rheology regulators, and uses 30% hydrogen peroxide as a foaming agent. The water meets the requirements for concrete mixing water. The foaming process adopts unique variable temperature foaming to achieve balanced stability of slurry expansion and hardening under mild conditions.

[0068] An assembled energy-saving thermal insulation board based on variable temperature foaming and a preparation method thereof, comprising the following steps:

[0069] (1) Solid waste-based sulfur-aluminum-iron cementitious clinker is made from coal gangue, red mud, aluminum ash, carbide slag, and by-product gypsum by calcining at 1180℃ for use.

[0070] (2) taking 10 parts of the solid waste-based sulfur-aluminum-iron cemented clinker in (1), 80 parts of blast furnace slag powder, 6 parts of silica fume, and 2 parts of calcium carbide slag, grinding and premixing them, and the fineness requirement is to meet the sieve residue of 200 mesh square hole sieve less than 10%;

[0071] (3) Add 1.2 parts of calcium stearate, 0.1 parts of xanthan gum, and 1 part of dispersible latex powder to the mixture in (2), mix well and set aside;

[0072] (4) 10 parts of original by-product gypsum, 0.6 parts of polycarboxylate water-reducing agent, 0.4 parts of chopped fibers, 0.02 parts of composite retarder, and 40 parts of water were mixed and stirred by a wet method for later use;

[0073] (5) The mixture in (3) is mixed into the water-containing mixture in (4), first stirred at a slow speed (145 r / min) for 30 seconds, and then stirred at a high speed (285 r / min) for 3 minutes to prepare a mixed slurry;

[0074] (6) The mixed slurry in (5) was slowly stirred (145 r / min), and 5 parts of hydrogen peroxide was added during the slow stirring process, and then stirred at a high speed (285 r / min) for 1 min;

[0075] (7) The fresh slurry mixed in (6) is poured into a board mold box, and the mold box is covered with plastic wrap. The board temperature is maintained at 60°C for 12 hours by external heating. The assembled energy-saving thermal insulation material is finally demolded after expansion and hardening. After that, the assembled energy-saving thermal insulation board is obtained by proper curing in a standard curing room.

[0076] Comparative Example 1

[0077] The difference from Example 1 is that solid waste-based sulphur-aluminium-iron cementitious clinker is not used, and the amount of blast furnace slag powder is adjusted to 80 parts.

[0078] The test results show that solid waste-based sulfur-aluminum-iron cementitious clinker is a core material. Its main function is to improve the early compressive strength of the material and enhance the stability of the early foam structure. Failure to use this material will result in an inability to quickly solidify and form in the early stage, and the occurrence of mold collapse.

[0079] Comparative Example 2

[0080] The difference from Example 1 is that the original by-product gypsum is not used, and the amount of solid waste-based sulfur-aluminum-iron cementitious clinker is adjusted to 40 parts.

[0081] The test results show that the role of gypsum is to provide sufficient calcium sulfate to the gelling system to promote the hydration process, and on the other hand, it also has the effect of reducing costs. Without adding original gypsum, the system lacks calcium sulfate required for hydration, which can easily lead to unstable conversion of AFt in the system into AFm, etc., thus affecting the performance.

[0082] Comparative Example 3

[0083] The difference from Example 1 is that hydroxypropyl cellulose ether is used instead of xanthan gum.

[0084] The test results show that xanthan gum can enhance the cohesion of the slurry, reduce foam agglomeration, and control the size of the foam. Although hydroxypropyl cellulose ether has similar effects, the effect of xanthan gum is more obvious at the same dosage.

[0085] Comparative Example 4

[0086] The difference from Example 1 is that no dispersible latex powder is added.

[0087] The test results show that latex powder can reduce the surface tension of the slurry, which is beneficial to reducing foaming resistance. In addition, its film-forming property can further strengthen the pore wall structure, improve the integrity of the pore wall, and reduce water absorption.

[0088] Table 1 High-performance, low-energy solid waste-based energy-saving thermal insulation materials prepared in Example

[0089]

[0090] Table 2 Comparative Examples of High-Performance, Low-Energy Consumption Solid Waste-Based Energy-Saving and Thermal Insulation Materials

[0091]

[0092]

[0093] From the comparison between Example 1 and Comparative Example 1, it can be seen that the solid waste-based sulfur-aluminum-iron cementitious clinker effectively improves the strength of the thermal insulation board and reduces the water absorption and thermal conductivity.

[0094] From the comparison between Example 1 and Comparative Example 2, it can be seen that the addition of original by-product gypsum improves the strength of the thermal insulation board.

[0095] From the comparison between Example 1 and Comparative Example 3, it can be seen that compared with hydroxypropyl cellulose ether, the use of xanthan gum can better improve the strength of the thermal insulation board and reduce the water absorption rate.

[0096] From the comparison between Example 1 and Comparative Example 4, it can be seen that the addition of dispersible latex powder improves the strength of the insulation board to a certain extent and reduces the water absorption and thermal conductivity.

[0097] It can be seen that the present invention achieves a high degree of matching between the strength development of solid waste-based cementitious materials and the foaming and expansion process of foam slurry through variable temperature control. Secondly, the present invention gets rid of the high energy consumption and carbon emission autoclave curing process, and achieves performance improvement and foaming expansion of energy-saving insulation boards under mild conditions. Thirdly, the present invention solves the problems of mixing, pouring and molding of assembled energy-saving insulation boards, and further improves the molding accuracy of products. Finally, the present invention solves the problem of comprehensive utilization of bulk industrial solid waste.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An assembled energy-saving thermal insulation board based on variable temperature foaming, characterized in that: The invention is composed of the following raw materials in parts by mass: 60-80 parts of blast furnace slag powder, 10-20 parts of solid waste-based sulfur-aluminum-iron gelled clinker, 10-25 parts of original by-product gypsum, 2-6 parts of silica fume, 0.5-2 parts of carbide slag, 0.5-1.2 parts of calcium stearate, 0.2-0.6 parts of polycarboxylate water reducer, 0.02-0.1 parts of xanthan gum, 0.2-1 parts of dispersible latex powder, 0.1-0.5 parts of chopped fibers, 0.02-0.06 parts of composite retarder, and foaming agent. Wherein, the foaming agent is a hydrogen peroxide solution with a mass concentration of 30%-33%, and the amount used is 2-5% of the total mass of the gelling material.

2. The assembled energy-saving thermal insulation board based on variable temperature foaming according to claim 1 is characterized in that: The water-cement ratio is 0.3-0.

4.

3. The assembled energy-saving thermal insulation board based on variable temperature foaming according to claim 1, characterized in that: The solid waste-based sulfur-aluminum-iron cementitious clinker is prepared by using coal gangue, red mud, aluminum ash, carbide slag and by-product gypsum as raw materials and being calcined at a low temperature of 1200-1250°C.

4. The assembled energy-saving thermal insulation board based on variable temperature foaming according to claim 1, characterized in that: The composite retarder consists of boric acid, citric acid and tartaric acid, and the composition ratio is 1:1:

2.

5. The assembled energy-saving thermal insulation board based on variable temperature foaming according to claim 1, characterized in that: The material of the chopped fibers is polypropylene fiber or glass fiber, with a length of 6-12mm.

6. A method for preparing an assembled energy-saving thermal insulation board based on variable temperature foaming, characterized in that: include: Solid waste-based sulfur-aluminum-iron cementitious clinker, blast furnace slag powder, silica fume, and carbide slag are ground separately and premixed to obtain a first mixed material; Adding calcium stearate, xanthan gum, and dispersible latex powder to the first mixed material, and mixing them evenly to obtain a second mixed material; The original by-product gypsum, polycarboxylate water reducer, chopped fibers, composite retarder and water are wet-mixed uniformly at a water-cement ratio of 0.3-0.4 to obtain a water-containing mixture; The second mixed material is mixed with the water-containing mixed material, firstly stirred at a slow speed for 30-40 seconds, and then stirred at a high speed for 3-4 minutes to obtain a mixed slurry; wherein, during the slow stirring process, hydrogen peroxide is added, and then stirred at a high speed for 1 minute; The mixed slurry is poured into a board mold box, and after the mold box is covered with a film, the board temperature is maintained at 40-60° C. for 12-24 hours by external heating, demolded, and cured.

7. The method for preparing the assembled energy-saving thermal insulation board based on variable temperature foaming according to claim 6, characterized in that: The fineness of the first mixed material is that the residue on a 200-mesh square sieve is less than 10%.

8. The method for preparing the assembled energy-saving thermal insulation board based on variable temperature foaming according to claim 6, characterized in that: The rotation speed of the slow stirring is 140±5 r / min.

9. The method for preparing the assembled energy-saving thermal insulation board based on variable temperature foaming according to claim 6, characterized in that: The rotation speed of the high-speed stirring is 280±10r / min.

10. Application of the assembled energy-saving thermal insulation board based on variable temperature foaming according to any one of claims 1 to 5 in the field of construction.

Citation Information

Patent Citations

  • Method for quickly manufacturing foam cement heat-insulation plate

    CN102633520A

  • Preparation method of foamed cement insulation boards

    CN102863194A

  • Method for producing foamed thermal insulation material

    CN107759186A

  • Waste concrete recycled foam cement insulation board and preparation method thereof

    CN111138145A

  • Desulfurized gypsum retarder, preparation method thereof, and application thereof in sulphoaluminate cement

    CN113683333A